-2=6x-2(x+19)

Simple and best practice solution for -2=6x-2(x+19) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2=6x-2(x+19) equation:


Simplifying
-2 = 6x + -2(x + 19)

Reorder the terms:
-2 = 6x + -2(19 + x)
-2 = 6x + (19 * -2 + x * -2)
-2 = 6x + (-38 + -2x)

Reorder the terms:
-2 = -38 + 6x + -2x

Combine like terms: 6x + -2x = 4x
-2 = -38 + 4x

Solving
-2 = -38 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-2 + -4x = -38 + 4x + -4x

Combine like terms: 4x + -4x = 0
-2 + -4x = -38 + 0
-2 + -4x = -38

Add '2' to each side of the equation.
-2 + 2 + -4x = -38 + 2

Combine like terms: -2 + 2 = 0
0 + -4x = -38 + 2
-4x = -38 + 2

Combine like terms: -38 + 2 = -36
-4x = -36

Divide each side by '-4'.
x = 9

Simplifying
x = 9

See similar equations:

| 8x-2(7x+13)+9=5-4 | | -6(10-4f)=-3(-12+8f) | | (1.5x+20)+2x=90 | | 205=-7x-2(6x-17) | | -3/4w=-9 | | -6.5x=14.2 | | 8/9-8/9 | | t/5-7=10 | | 21=5x-4(x-7) | | 4x^2-48+108=0 | | x/6-1/5= | | x-4y=19fory | | 36=216n | | 3x+22=12x-15 | | -244=3x+7(-4x-17) | | 10(-5)= | | lnx=0.6 | | -1+4(2z-1)=3 | | 3x-70=260 | | 21x^2+192x+180=0 | | 12f-3f= | | 61=42-13 | | -231=-4x+5(3x-22) | | 6-5i/-2i | | 15-3(4x+6)=11-4x | | 3(9c+2)= | | (5/9)^2 | | 10sinx=-5 | | -5x1/5-7 | | 3x+4(6x+11)=206 | | 6x-9=2x+11 | | -2x-3(x+17)=-91 |

Equations solver categories